2016
DOI: 10.5483/bmbrep.2016.49.12.180
|View full text |Cite
|
Sign up to set email alerts
|

Misexpression of AtTX12 encoding a Toll/interleukin-1 receptor domain induces growth defects and expression of defense-related genes partially independently of EDS1 in Arabidopsis

Abstract: In this study, a tissue-specific GAL4/UAS activation tagging system was used for the characterization of genes which could induce lethality when ubiquitously expressed. A dominant mutant exhibiting stunted growth was isolated and named defective root development 1-D (drd1-D). The T-DNA tag was located within the promoter region of AtTX12, which is predicted to encode a truncated nucleotide-binding leucine-rich repeat (NLR) protein, containing a Toll/interleukin-1 receptor (TIR) domain. The transcript levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…NONRACE-SPECIFIC DISEASE RESISTANCE 1 (NDR1), a membrane-associated integrin-like protein, plays a similar role for CC-NLRs (Century et al 1997; Knepper et al 2011; Coppinger et al 2004; Century et al 1995). To investigate whether disruption of EDS1 or NDR1 are required for dwarfing or cell death observed in MSL10-GFP overexpression lines or the msl10-3G background, we introduced 35S:MSL10-GFP into the eds1-23 (SALK_057149, (Song 2016)) and the ndr1-1 (Century et al 1997) null mutant backgrounds by transformation. As anticipated, expression of 35S:MSL10-GFP in wild-type plants resulted in severe dwarfing and the appearance of yellowish-brown lesions on rosette leaves ( Figure 4A, top panels ), and Trypan blue-stained patches on leaves ( Figure 4A, bottom panels ) compared to the wild type or to untransformed eds1-23 or ndr1-1 mutants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…NONRACE-SPECIFIC DISEASE RESISTANCE 1 (NDR1), a membrane-associated integrin-like protein, plays a similar role for CC-NLRs (Century et al 1997; Knepper et al 2011; Coppinger et al 2004; Century et al 1995). To investigate whether disruption of EDS1 or NDR1 are required for dwarfing or cell death observed in MSL10-GFP overexpression lines or the msl10-3G background, we introduced 35S:MSL10-GFP into the eds1-23 (SALK_057149, (Song 2016)) and the ndr1-1 (Century et al 1997) null mutant backgrounds by transformation. As anticipated, expression of 35S:MSL10-GFP in wild-type plants resulted in severe dwarfing and the appearance of yellowish-brown lesions on rosette leaves ( Figure 4A, top panels ), and Trypan blue-stained patches on leaves ( Figure 4A, bottom panels ) compared to the wild type or to untransformed eds1-23 or ndr1-1 mutants.…”
Section: Resultsmentioning
confidence: 99%
“…Arabidopsis thaliana plants used in this study were of the Col-0 ecotype. The following mutants were used: sid2-2 (Wildermuth et al 2001)(Wildermuth et al, 2001)(Wildermuth et al, 2001), pad4-1 (Jirage et al 1999), eds1-23 (SALK_057149; (Song 2016), rar1-21 (Tornero et al 2002), sgt1b-2 (GABI_857A04; (Zhang et al 2015)), sgt1b-1 (SALK_026606), ndr1-1 (Century et al 1997), ( hsp90.1-1 (SALK_007614; (Takahashi et al 2003)), fls2 (salk_141277; (Guo et al 2014)), msl10-1 (SALK_114626), msl10-3G (Zou et al 2016; Basu et al 2020), and msl9-1 (SALK_114361; (Haswell et al 2008)). In most experiments, plants were grown on soil at 21°C under a 24-h light regime (~120 μmol m -2 s -1 ).…”
Section: Methodsmentioning
confidence: 99%
“…In this context, the cell death activity of the A. thaliana TNL RPS4 is also strictly dependent on its protein level in plants 54 . Moreover, in an activation-tagging system, a DNA tag in the promoter region of A. thaliana TX12 enhances expression of this TIR -only gene and activates EDS1 -dependent immune responses 55 , suggesting that upregulation of TIR protein expression is sufficient for their activation. A similar activation mechanism might be used by TIRs that are transcriptionally induced during PTI 10 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some Arabidopsis genes that were originally classi ed as TX need to be reclassi ed as TIR genes. AtTX12 (AT2G03300) encodes a 203 aa-long protein classi ed as TX, which results in the activation of defense signaling and growth defects (Song, 2016). The relatively short C-terminal extension (aa 165-204) in AtTX12 does not show any sequence similarity to known protein domains in the conserved domain database (https://www.ncbi.nlm.nih.gov/cdd) and is, therefore, more appropriate for classi cation as a TIR-only protein.…”
Section: Discussionmentioning
confidence: 99%
“…In a model plant, Arabidopsis thaliana (Arabidopsis), a total of 145 genes encoding TIR domain-containing proteins were identi ed (Meyers et al 2003): 83 TNLs, 5 TNLXs, 2 TNTNLs, 2 TTNLs, 21 TNs including one pseudogene, 30 TXs including 3 pseudogenes, and 2 XTNXs. It has been reported that overexpression of TX or TIR alone, such as AtTX12 and AtRBA1, can also induce elevated defense responses or cell death (Nandety et al 2013;Nishimura et al 2017;Song 2016).…”
Section: Introductionmentioning
confidence: 99%